2020
DOI: 10.1007/s10815-020-02011-1
|View full text |Cite
|
Sign up to set email alerts
|

Live birth outcomes in infertile patients with class III and class IV obesity following fresh embryo transfer

Abstract: Objective Assess the effect of class III (body mass index [BMI, kg/m 2 ] 40-49.9) and class IV obesity (≥ 50) on clinical pregnancy and live birth outcomes after first oocyte retrieval and fresh embryo transfer cycle. Design Cohort study Setting Academic center Patients Patients undergoing their first oocyte retrieval with planned fresh embryo transfer in our clinic between 01/01/2012 and 12/31/2018. Patients were stratified by BMI: 18.5-24.9 (n = 4913), 25-29.9 (n = 1566) 30-34.9 (n = 559), 35-39.9 (n = 218),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…One of the complications described during pregnancy in obese women is a higher risk of early and late miscarriage [26,27 ▪ ] in both natural and assisted conception [13,28,29], which increases in a BMI-dependent manner [30], and can be reiterative, as in the case of recurrent miscarriage [31]. A recent dose–response meta-analysis [15] in which 13 studies and 235 167 cycles were included in the analysis of miscarriage rates observed a risk ratio of miscarriage of 1.09 [95% confidence interval (CI): 1.05–1.12] per 5-unit increment in BMI.…”
Section: Miscarriage Risk In Obese Womenmentioning
confidence: 99%
“…One of the complications described during pregnancy in obese women is a higher risk of early and late miscarriage [26,27 ▪ ] in both natural and assisted conception [13,28,29], which increases in a BMI-dependent manner [30], and can be reiterative, as in the case of recurrent miscarriage [31]. A recent dose–response meta-analysis [15] in which 13 studies and 235 167 cycles were included in the analysis of miscarriage rates observed a risk ratio of miscarriage of 1.09 [95% confidence interval (CI): 1.05–1.12] per 5-unit increment in BMI.…”
Section: Miscarriage Risk In Obese Womenmentioning
confidence: 99%
“…There is an essential role of obesity in treatment outcomes in women with PCOS in the interaction with HA. For patients undergoing IVF or intracytoplasmic sperm injection, Romanski et al [ 31 ] showed a significant trend for a decreased LBR and increased miscarriage rate as BMI increased. Furthermore, patients with a BMI >40 kg/m 2 had worse IVF treatment outcomes than normal-weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…One effective way to treat endometriosis is to use GnRH agonists (such as leuprolide acetate), which inhibit estrogen production. However, one of the possible side effects of this treatment is obesity and BMI increasing, which is a concern for some patients (23,24). This study investigated the role of leuprolide acetate in treating overweight patients (BMI≥30) and their comparison with non-overweight patients (BMI<30) for six months.…”
Section: Evaluation Of Mif Gene Expressionmentioning
confidence: 99%